Analisa Platform Library Steam Sebagai Data Aset Manajemen - Egi Abinowi; Dudih Gustian (CV. Indie Press Edutaste, 2025)
Data has transformed into a strategic asset with high economic value, especially in the gaming industry through digital distribution platforms such as Steam. This study aims to analyze the Steam library platform as a form of Data Asset Management (DAM) implementation. Through a review of various library features, this study explores how user interactions including purchase history, playtime, achievements, and genre preferences are managed as structured digital asset data units. The analysis shows that Steam performs the main functions of asset management which include storing, managing, utilizing, and analyzing data to generate added value for users and the company. This data utilization is realized through personalized services, such as the